Biofertilizers based on beneficial microorganisms and organic matter: a systematic review - Mamani, Amelia (Revista Acciones Médicas, 2023)
Biofertilizers based on efficient microorganisms and organic matter are emerging as a promising element to curb the indiscriminate use of synthetic fertilizers. However, a deeper understanding of them is needed, along with knowledge of their effects on crops. Thus, the objective was to identify studies analyzing the importance of biofertilizers. Methodologically, the PRISMA guidelines were employed, with inclusion criteria covering studies from 2001 to 2023 related to biofertilizers, associated with biotechnology, and available in Open Access format. Databases such as Scielo, Scopus, Google Scholar, Redalyc, and Dialnet were utilized. As a result, 20 documents were retrieved and analyzed, categorizing them by publication year, country of origin, and study objective. The conclusion was that studies on the subject have seen a notable increase in recent years. Soil preservation is crucial for future food sustainability. Biofertilizers maintain soil health, and current technology allows for detailed research on the interaction of microorganisms with residues. Mexico and Peru are seeking sustainable alternatives, while in Cuba, Ecuador, and Costa Rica, governments support biofertilizer research, promoting their use and proper management of organic waste to enhance agricultural production.